Effect of Acetaminophen (APAP) on Physiological Indicators in Lactuca sativa - Jiri Kudrna; Frantisek Hnilicka; Jan Kubes; Pavla Vachova; Helena Hnilickova; Margita Kuklova (Life, 2020)
This study analyzes the effects of acetaminophen (APAP) as a contaminant on physiological characteristics of lettuce plants (Lactuca sativa L.). Experiments were provided in an experimental greenhouse with semi-controlled conditions. The effect of different amounts of contaminant was evaluated by using regression analysis. Plants were grown in five concentrations of APAP: 0 µM, 5 µM, 50 µM, 500 µM, and 5 mM for 14 days in two variants, acute and chronic. The obtained results show that the monitored parameters were demonstrably influenced by the experimental variant. Plants are more sensitive to chronic contamination compared to acute. Significant (p < 0.05) deviation in photosynthesis and fluorescence was observed compared to the control in different variants. The highest doses of APAP reduced the intensity of photosynthesis by a maximum of more than 31% compared to the control. A reduction of 18% was observed for the fluorescence parameters. Pronounced correlation was described between chlorophyll fluorescence parameters and yield mainly under APAP conditions. The amount of chlorophyll was influenced by exposure to APAP.